2023
DOI: 10.21037/apm-23-56
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of the 30-day expected mortality metric in palliative radiation treatment: a narrative review

Abstract: Background and Objective: The 30-day expected mortality rate is frequently used as a metric to determine which patients benefit from palliative radiation treatment (RT). We conducted a narrative review to examine whether its use as a metric might be appropriate for patient selection.Methods: A literature review was conducted to identify relevant studies that highlight the benefits of palliative RT in timely symptom management among patients with a poor performance status, the accuracy of predicting survival ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…While there is evidence to support using 30 day mortality following PRT as a quality metric for centres, it remains that for some patients, single fraction PRT within 30 days of death will be appropriate to palliate pain or bleeding. This has been discussed in depth in a narrative review by Navarro‐Domenech et al 29 . and case by case appropriateness of treatment can be easily evaluated in individual centres within morbidity and mortality meetings.…”
Section: Discussionmentioning
confidence: 99%
“…While there is evidence to support using 30 day mortality following PRT as a quality metric for centres, it remains that for some patients, single fraction PRT within 30 days of death will be appropriate to palliate pain or bleeding. This has been discussed in depth in a narrative review by Navarro‐Domenech et al 29 . and case by case appropriateness of treatment can be easily evaluated in individual centres within morbidity and mortality meetings.…”
Section: Discussionmentioning
confidence: 99%
“…Because these models have limited accuracy, particularly for predicting whether patients will die within the next 30 days, some authors have discouraged the routine use of the 30-DM as the only metric to decide whether to offer PRT, particularly in painful bone metastases, spinal cord compression and hemostatic treatments. For these indications, several trials have demonstrated substantial response rates by four weeks and sometimes within the first two weeks after PRT [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally considered that such patients are unlikely to benefit from palliative RT before succumbing, although a recent review from international experts questions this assumption when the measure is used predictively ('expected' 30-day mortality). 5 A 2022 meta-analysis found an overall (retrospective) 30-day mortality rate of 16% (95% CI = 14-18%), proposed as a baseline for future comparisons between individual centres. However, not surprisingly, sub-group analysis did identify various factors resulting in higher mortality (e.g.…”
Section: Question 1: Whether To Treat?mentioning
confidence: 99%